2015
DOI: 10.12659/msm.893856
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Gastrectomy in Node-Negative Gastric Cancer: A Review and Meta-Analysis of Prognostic Factors

Abstract: BackgroundLymph node metastasis is one of the most important prognostic factors for survival of patients with gastric cancer (GC) after surgical resection. Nevertheless, a considerable number of patients have node-negative disease. We performed the present systematic review to evaluate survival and identify prognostic factors in node-negative GC patients undergoing curative intent resection.Material/MethodsRelevant studies published between January 2000 and January 2015 were identified by searching the PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This can be regarded as indirect evidence for their predictive power in gastric cancer prognosis. Direct evidence, i.e., magnitude of their association with the outcome, such as hazard ratio, can be found in previous systematic reviews and meta-analyses [46, 47]. Therefore, we suggest that future model development, if necessary, to build upon these existing evidence.…”
Section: Discussionmentioning
confidence: 79%
“…This can be regarded as indirect evidence for their predictive power in gastric cancer prognosis. Direct evidence, i.e., magnitude of their association with the outcome, such as hazard ratio, can be found in previous systematic reviews and meta-analyses [46, 47]. Therefore, we suggest that future model development, if necessary, to build upon these existing evidence.…”
Section: Discussionmentioning
confidence: 79%
“…Previous reports consistently found that the depth of invasion was an independent predictor in node-negative GC that included early gastric cancer (EGC) [7] . Furthermore, there is no consensus about other clinicopathologic factors of the prognostic signi cance, including patient gender, age, tumor location, tumor size, histological grading, Lauren type and Lymphatic vessel invasion [8,9] . In addition, little is known about the recurrent patterns of node-negative AGC after D2 curative resection.…”
Section: Introductionmentioning
confidence: 99%
“…The TNM classification consists of tumor depth, nodal and distant metastasis with distant metastasis as the strongest prognostic marker [ 4 ]. The classification also includes peritumoral lymphatic and venous invasions, which are linked to aggressive tumor behavior in gastric cancer [ 5 , 6 ]. Additional biomolecular prognostic markers are currently being investigated by several clinical researchers.…”
Section: Introductionmentioning
confidence: 99%